THE EFFECT OF REGIONAL ORIGINAL REVENUE (PAD), GENERAL ALLOCATION FUNDS (DAU), AND SPECIAL ALLOCATION FUNDS (DAK) ON SUSTAINABLE REGIONAL ECONOMIC GROWTH (PED) IN THE SOUTHERN SUMATRA REGION (SUMBAGSEL) - Rangga Ananta; Heni Noviarita; Alief Rakhman Setyanto (JURNAL ECONOMICA : Research of Economic And Economic Education, 2026)
This study examines the effect of Regional Own-Source Revenue (PAD) inequality, General Allocation Funds (DAU), and Special Allocation Funds (DAK) on sustainable Regional Economic Growth (PED) in the Southern Sumatra region. The urgency of this study arises from persistent fiscal inequality among regions and the uneven effectiveness of fiscal decentralization in promoting inclusive economic growth. This study aims to analyze the partial and simultaneous effects of PAD inequality, DAU, and DAK on regional economic growth, as well as to examine their implications from the perspective of Islamic economic values. This research uses a quantitative approach with panel data consisting of five provinces in Southern Sumatra during the 2020–2024 period. The data were obtained from the Central Statistics Agency and analyzed using panel data regression with model selection tests, including Chow, Hausman, and Lagrange Multiplier tests. The results show that PAD inequality has no significant effect on PED, while DAU has a negative and significant effect. In contrast, DAK has a positive and significant effect on PED, indicating that targeted fiscal transfers are more effective in supporting regional economic activity. Simultaneously, PAD inequality, DAU, and DAK significantly affect PED, with an adjusted R² of 51.11%. These findings imply that regional fiscal policy should prioritize productive spending, especially through the optimization of DAK, while strengthening fiscal governance based on justice, accountability, and public welfare as reflected in Islamic economic values